641 Risky driving, unsafe vehicles and car crash injury: a population-based case-control study in Fiji. (1st September 2016) - Wainiqolo, Iris; Kool, Bridget; Kafoa, Berlin; Herman, Josephine; McCaig, Eddie; Ameratunga, Shanthi
Abstract : Background: Risky driving and unsafe vehicles are two areas receiving increased global attention as priorities for road traffic injury prevention. However, the attendant risks have not been quantified in low- and middle-income Pacific nations using controlled epidemiological studies. Methods: A population-based case-control study was designed to include all four-wheeled motor vehicles involved in crashes where at least one occupant died or was hospitalised (case vehicles) and a random sample of vehicles driven on roads in Viti Levu, Fiji (control vehicles). The drivers or their proxies were administered structured questionnaires eliciting self-reported data on risky driving and vehicle factors, including crash involvement and traffic convictions in the previous five years. Results: Drivers of 154 case and 752 control vehicles participated in this study. Multivariable models of the main effects of interest found significant excess in the odds of injury-involved motor vehicle crashes (MVCs) with vehicles older than 10 years (OR 1.99; 95% CI: 1.27–3.12); vehicles with seat belts only in the front seats (OR 2.03; 95% CI: 1.19–3.46) and speeding up when someone tries to pass (OR 3.40; 95% CI: 1.51–7.65). The odds of MVC were significantly less if drivers had experienced a traffic conviction or crash in the previous 5 years (OR 0.43; 95% CI: 0.24–0.78 and OR 0.45; 95% CI: 0.22, 0.95, respectively). Conclusions: Speeding in some contexts and driving vehicles older than 10 years or without a full complement of seatbelts were associated with a 2–3 fold increase in the odds of serious injury-involved MVCs. In contrast to some other studies, previous traffic convictions and crash involvement appeared protective, which may signify a greater deterrent effect. However, it is unclear if the apparent risk reduction will be long-lasting and we cannot exclude the possibility that this finding may reflect biases relating to social desirability or concerns relating to risk of prosecution.